ANALISIS PROMOSI DALAM MENINGKATKAN PENJUALAN PADA BENGKEL GLOBAL MOTOR SERVICE - Fadli, Mochammad Faisal; Steven, Steven (Jurnal Ekonomi Integra, 2025)
This study is entitled "Analysis of Promotions in Increasing Sales Turnover at Global Motor Service Workshops" with the problem "How Promotions Can Increase Sales Turnover at Global Motor Service Workshops."The variable in this research is a single variable, namely the promotion mix, with indicators: sales promotion, advertising, personal selling, direct marketing, and publicizing or public relations. The method used in this research is the descriptive-analytic method, namely a method that reveals the actual situation at the time the research was carried out based on facts, data collected, compiled, explained and then analyzed.The results of the promotion carried out through advertising are more attractive compared to other workshops. The methods used for sales promotion include relatively cheap spare parts prices, issuing and distributing lots of stickers and calendars. In this personal selling the promotions carried out are through mechanics or mechanics, namely when consumers come to repair their damaged vehicles. In direct marketing, promotions carried out include always providing original spare parts and spare parts are always available, and promotions carried out in public relations include always taking part in activities. charity, is always seen in every sporting activity of the community youth organization